2018
DOI: 10.1016/j.jtho.2018.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Proteogenomic Analysis of Surgically Resected Lung Adenocarcinoma

Abstract: Our results suggest that mRNA and protein data possess independent biological and clinical importance, which can be leveraged to create higher-powered expression biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
(48 reference statements)
0
19
0
Order By: Relevance
“…The three CPTAC flagship reports on colorectal 23 , breast 24 , and ovarian 25 cancers, respectively, have provided a resource to the cancer research community, both by indicating which of the genomic and transcriptomic features associated with these cancers was recapitulated at the protein level, and by providing new insights into the substantial effects of post-translational modifications, specifically phosphorylation and acetylation, on the functional activities associated with DNA repair, proliferation, and survival. The proteogenomic approach has also been applied to other cancer studies based on tumor specimens, patient-derived xenograft (PDX) models, or cell lines 2633 . There have been multiple reviews on the concept and methods of proteogenomics and its application to cancer research 3442 .…”
Section: Proteogenomics-driven Target Discovery: Added Value Of Protementioning
confidence: 99%
“…The three CPTAC flagship reports on colorectal 23 , breast 24 , and ovarian 25 cancers, respectively, have provided a resource to the cancer research community, both by indicating which of the genomic and transcriptomic features associated with these cancers was recapitulated at the protein level, and by providing new insights into the substantial effects of post-translational modifications, specifically phosphorylation and acetylation, on the functional activities associated with DNA repair, proliferation, and survival. The proteogenomic approach has also been applied to other cancer studies based on tumor specimens, patient-derived xenograft (PDX) models, or cell lines 2633 . There have been multiple reviews on the concept and methods of proteogenomics and its application to cancer research 3442 .…”
Section: Proteogenomics-driven Target Discovery: Added Value Of Protementioning
confidence: 99%
“…Consequently, numerous additional prognostic or predictive factors [ 5 7 ], among image-derived parameters [ 8 12 ], have been investigated aiming at more differentiated outcome prediction and more differentiated management decisions. Among parameters from positron emission tomography/computed tomography with [ 18 F]fluorodeoxyglucose (FDG-PET/CT), asphericity (ASP) is a parameter that reflects shape irregularity of the primary tumor’s metabolic tumor volume (MTV), combining metric and metabolic features of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, proteogenomic analysis has become a powerful tool for cancer research and several studies on lung cancer have been reported. In a recent study, Sharpnack et al (2018) established a novel analysis about the co-relation between mRNA and proteins and predicted 51 potential biomarkers for lung cancer. Treue et al (2019) reported EGFRmutated NSCLC with whole exome sequencing data, phosphorylated protein data and computational models, and identified three potential biomarkers for therapy targets.…”
mentioning
confidence: 99%